Genetic components of the traits of prolificacy and mortality at birth in a diallel cross between five rabbit breeds - Garc?a, Yoleisy; Ponce de Le?n, Raquel; Mastache, A. A.; Guzm?n, Gladys (Cuban Journal of Agricultural Science, 2011)
Two hundred and fifty reproductive observations of a balanced diallel experiment were used with five rabbit breeds: California (C), Caoba (Cao), Chinchilla (Ch), New Zeland (N) and Semigiant (S) to determine the effect of the cross and of the genetic components of general combinatory (GCC) and specific combinatory (SCC) capacity, maternal (ME) and reciprocal (RE) effects of the 20 resulting F1 crosses, for the traits total births (TB), live births (LB) and mortality at birth (MORTB). The experiment took place between May 2003 and April 2004. In the statistical analysis, the procedures of GLM (Modelo Lineal General) and IML (Interactive Language of Matrixes) of SAS (2007) were applied. The former was used to determine the effect of the cross, and the latter to estimate the best linear unbiased predictors (BLUP) of the different genetic components through the model of the design 3 of Griffing (1956a). The components of variance were determined through the method III of Henderson, but all were very low and next to 0. The cross affected the TB and the MORTB, whereas out of the genetic components only the GCC had significant effect on the last trait. The best specific crosses for TB were the S.Ch and the Cao. S, with six young rabbits, which surpassed to N. Cao, N.Ch and Ch. N (5.8 young rabbits). The best GCC was exploited by the use of the New Zealand breed to diminish the mortality at birth and, in accordance with this; the greatest advantages were attained with the specific crosses N.C and N. Cao. However, the non-additive genetic variance was not significant for this trait, due to the similarity of the breeds. Key words: diallel cross, rabbits, genetic components, BLUP.